Perception of students and teachers regarding the attributes of an effective clinical teacher in dentistry: a cross-sectional analytical study - Sultan, Rooha; Azim, Rubaba; Adnan, Nooreen; Khan, Sohail Ahmed; Saleem, Omema (Journal of the Pakistan Medical Association, 2024)
Objectives: To compare the perception of dental students and faculty members regarding the attributes of effective clinical teachers. Method: The cross-sectional study was conducted at the Dow University of Health Sciences, Karachi, from August 2021 to November 2021, and comprised third and final year dental students and associated clinical faculty members from in three dental colleges in the city. Data was collected using the modified version of a pre-validated questionnaire. Data was analysed using SPSS 25. Results: Of the 200 students approached, 169(84.5%) responded; 135(79.9%) females and 34(20.1%) males with mean age 21.78±1.099 years (range: 19-26 years). Of the 59 teachers approached, 49(83%) responded; 33(67.3%) females and 16(32.7%) males with mean age 31.59±5.041 years (range: 23-49 years). The students found record-keeping a tiresome task (42%), while teachers regarded it essential for clinical development. Unlike teachers, the students were unable to identify the relevance of clinical objectives and they also did not appreciate teachers’ involvement in clinical procedures. For other domains regarding personal traits, teaching methods and clinical skills, both groups had similar responses. Conclusion: There was generally a similarity of opinions among students and teachers regarding the essential qualities of effective dental clinical teaching. Key Words: Dental education, Clinical teaching, Competent clinical teacher.